PENGENALAN GREEN ACCOUNTNG DAN GAYA HIDUP PEDULI LINGKUNGAN PADA GENERASI Z DI SMAN 1 TIRTAYSA - Dian Rusdiana (TRIDAYA: Jurnal Pengabdian kepada Masyarakat, 2025)
The needs in daily life are increasingly diverse, various groups with various different needs either in meeting their satisfaction to achieve maximum or basic needs that must be met. In an effort to achieve success in business, the Company wants profits for its business, however, sometimes it is negligent in controlling waste on the profits it gets. We as students of Pamulang Serang University are pioneers in preventing environmental pollution because it can be bad for human health and life. This activity aims to realize how important the role of humans is to the environment, therefore the existence of PKM activities provides education related to green accounting, especially for generation z which is expected to bring positive changes for the future. SMAN 1 Tirtayasa is an option to carry out Community Service activities where we convey the concept, benefits, goals, and practices related to green accounting. This activity will be held on May 27, 2024 at SMAN 1 Tirtayasa with a total of 35 students majoring in social studies with the hope that when students can apply an attitude of caring for the environment and when entering the world of work can set aside part of the cost to manage waste from the company's production.